Misturas de ésteres produzidos a partir de fontes alternativas de triacilgliceróis : teor de ésteres e contaminantes - Melo, Josué Alves (2016)
In this study we identified the contaminants present in mixtures of methyl and ethyl esters of samples obtained from alternative sources of triacylglycerols, such as: Frying oil (OF), Cottonseed oil (OSA), Scum sludge (EE), Trap grease (GCG). The esters content (TE) of the samples were determined by gas chromatography with flame ionization detector (GC-FID) according to methodology NBR 15764. The samples presented TE below 96.5% (m/m), minimum percentage established by the National Agency of Petroleum, Natural Gas and Biofuels (ANP) to characterize the mixtures as Biodiesel. The identification of fatty acids methyl or ethyl esters (FAME or FAEE) in the mixtures were performed by gas chromatography/mass spectrometry (GC/MS), observing the presence of linear unsaturated esters with eighteen carbon atoms. By thermogravimetric profile, it was observed that the OF and OSA samples presented higher contamination by compounds of high molecular mass, approximately 12.00% (m/m), corroborating TE results. Reports in the literature indicate the processes of oxidative degradation or hydrolysis as being responsible for the origin of contaminants in these types of matrices, reinforced by the values of peroxide index obtained around 196.00 meq kg-1. By the easy ambiente sonic-spray ionization mass spectrometry technique (EASI-MS), in positive mode, it was possible to attribute the presence of dimers, confirmed by m/z 625, 673 and 689 ions, in addition to diacylglycerols (DAG) and triacylglycerols (TAG). The EE and GCG samples presented higher acid values around 28.00 mg KOH g-1 with higher contamination by free fatty acids (FFA). The FFA profile was determined by EASI-MS, in negative mode, and confirmed by derivatization of the samples with N,O-bis(trimethylsilyl)trifluoroacetamide (BSTFA) and posterior GC/MS analysis. The identified FFAs comprised a range of six to eighteen carbon atoms with the majority presence of palmitic, linoleic, oleic and stearic acid. In the optimization of the open column chromatography method (CC) for the gravimetric determination of ester and contaminant content in the esters mixtures, the use of the chromatographic column with a 6 mm internal diameter and the use of hexane:dichloromethane (7:3) to elute the esters, and the use of ethyl ether:acetonitrile (8:2) to elute the contaminants were ideal conditions obtained in the optimization of the CC method. The optimized method of CC was applied in all the samples of this work, and the apolar fraction obtained and representative of the esters had esters contents above 96.5% (m/m).